Appropriate care for neonates born to mothers with COVID‐19 disease. (10th July 2020) - Tran, Hoang Thi; Nguyen, Phuong Thi Kim; Huynh, Le Thi; Le, Chau Hoang Minh; Giang, Hoang Thi Nam; Nguyen, Phuong Thi Thu; Murray, John
Abstract: The global COVID‐19 pandemic has been associated with high rates of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) transmission, morbidity and mortality in the general population. Evidence‐based guidance on caring for babies born to mothers with COVID‐19 is needed. There is currently insufficient evidence to suggest vertical transmission between mothers and their newborn infants. However, transmission can happen after birth from mothers or other carers. Based on the currently available data, prolonged skin‐to‐skin contact and early and exclusive breastfeeding remain the best strategies to reduce the risks of morbidity and mortality for both the mother with COVID‐19 and her baby. Abstract :